2008
DOI: 10.1159/000167851
|View full text |Cite
|
Sign up to set email alerts
|

Metastasizing Renal Cell Carcinoma Developing in a Congenital Ectopic and Dysplastic Kidney

Abstract: We present the first case of a metastasizing renal cell carcinoma arising within a partially regressed multicystic dysplastic and ectopic left kidney in a 34-year-old patient. Despite nephrectomy and adjuvant immunotherapy, the patient died 4 months after diagnosis. Even though a recent systematic review found no evidence to support any of the different modalities for following up children with MCKD by ultrasound (Oxford Centre for Evidence-Based Medicine, Level of Evidence: 3a), our case supports the contrary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…There is no evidence for an increased risk of malignancy in MCDK in children and young adults; therefore, monitoring solely to exclude malignancy is unnecessary.-Despite case reports of various malignancies coinciding with MCDK (33)(34)(35)(36), numerous cohort studies with follow-up during childhood have not shown an increased risk of malignancy (Table E3 [online]).…”
Section: Simple Cystmentioning
confidence: 99%
“…There is no evidence for an increased risk of malignancy in MCDK in children and young adults; therefore, monitoring solely to exclude malignancy is unnecessary.-Despite case reports of various malignancies coinciding with MCDK (33)(34)(35)(36), numerous cohort studies with follow-up during childhood have not shown an increased risk of malignancy (Table E3 [online]).…”
Section: Simple Cystmentioning
confidence: 99%
“…No information regarding previous urological history or followup is provided. 35 The review authors felt the association probably occurred by chance IV. Cambio, in 2008, calculated that if the risk of RCC developing in a MCDK was equal to that of normal kidneys, there would be 10 cases of RCC in a MCDK per year in the USA.…”
Section: Renal Cell Carcinoma (Rcc) and Other Adult Renal Malignanciementioning
confidence: 99%
“…The present tumor appears not to be RCC arising from accessory kidney, because the tumor contained no renal tissue. A few cases of RCC occurring in accessory kidney have been reported 5 . In such cases, non‐neoplastic renal parenchyma and renal pelvis are present in addition to RCC 5 .…”
mentioning
confidence: 99%
“…A few cases of RCC occurring in accessory kidney have been reported. 5 In such cases, nonneoplastic renal parenchyma and renal pelvis are present in addition to RCC. 5 There is a possibility, however, that the present tumor arose from minute ectopic kidney.…”
mentioning
confidence: 99%
See 1 more Smart Citation